2002
DOI: 10.1016/s1357-2725(01)00123-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered liver gene expression in CCl4-cirrhotic rats is partially normalized by insulin-like growth factor-I

Abstract: We have previously shown that the administration of low doses of insulin-like growth factor-I (IGF-I) to CCl 4 -cirrhotic rats improves liver function and reduces fibrosis. To better understand the mechanisms behind the hepatoprotective effects of IGF-I, and to identify those genes whose expression is affected in cirrhosis and after IGF-1 treatment, we have performed differential display of mRNA analysis by means of polymerase chain reaction (PCR) in livers from control and CCl 4 -cirrhotic rats treated or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 52 publications
6
31
0
2
Order By: Relevance
“…Together, these data suggest an extramitochondrial protection of mitochondria, which is not fully understood. Previously, we reported that low doses of IGF-I restored the expression of several protease inhibitors such us ␣-1-antichymotripsin, the serine protease inhibitor 2 in cirrhotic rats (35), which could contribute to the described mitochondrial protection. In agreement with these results, it has been re- (28,29).…”
Section: Discussionmentioning
confidence: 85%
“…Together, these data suggest an extramitochondrial protection of mitochondria, which is not fully understood. Previously, we reported that low doses of IGF-I restored the expression of several protease inhibitors such us ␣-1-antichymotripsin, the serine protease inhibitor 2 in cirrhotic rats (35), which could contribute to the described mitochondrial protection. In agreement with these results, it has been re- (28,29).…”
Section: Discussionmentioning
confidence: 85%
“…In a related finding, IGF-1 has been shown to promote recovery from carbon tetrachloride-induced cirrhosis, by increasing DNA methylation and normalizing gene expression. 55 As illustrated in Figure 7, MS has two substrates, homocysteine and the dopamine D4 receptor in its homocysteine state. Dopamine-stimulated PLM, measured with [ 14 C]formate, reflects D4 receptor-directed MS activity and ethanol increases dopamine-stimulated PLM (Figure 4d), in contrast to its inhibition of homocysteine-directed MS activity (Table 1).…”
Section: Igf-1 and Dopamine Regulate Methionine Synthase M Waly Et Almentioning
confidence: 99%
“…In agreement with these results, it has been reported that IGF-I differentially regulates Bcl-xL and Bax. Previously, we reported that low doses of IGF-I restored the expression of several protease inhibitors such us the serine protease inhibitor 2 in cirrotic rats [137], which could contribute to the described mitochondrial protection. Our work provides new evidence of beneficial effect of IGF-I replacement therapy in degenerative diseases including aging.…”
Section: Discussionmentioning
confidence: 84%
“…Experimental model of cirrhosis: Male Wistar rats in which liver cirrhosis was inducted using CCl4. IGF-I therapy or saline was administrated the last 4 weeks [2,6,41,[137][138][139]. b.…”
Section: Aging and Others Conditions Of "Igf-i Deficiency" And Oxidatmentioning
confidence: 99%